2004
DOI: 10.1037/0022-0663.96.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Domain Specificity of Trilingual Teachers' Verbal Self-Concepts.

Abstract: Teachers from Hong Kong (N ϭ 437) responded to English, math, Cantonese, and Mandarin self-concept items. Confirmatory factor analysis found good support for the distinction of 4 domain-specific selfconcepts. English self-concept had a low correlation with Mandarin self-concept (r ϭ .09) and a negative correlation with Cantonese self-concept (r ϭ -.19). Cantonese and Mandarin, which presumably pertain to a single Chinese language domain, were also negatively correlated (r ϭ -.11). These very low correlations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
24
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 44 publications
12
24
2
2
Order By: Relevance
“…School self-concept was positively correlated with both reading and maths self-concepts (rs = .71 and .74 respectively) and with both non-academic self-concepts -art and physical self-concepts (rs = .46 and .42 respectively). The correlation between reading and maths self-concepts are high (r = .48), compared to previous research (e.g., Yeung & Lee, 1999;Yeung & Wong, 2004), but this was consistent with the prediction that they would be clearly distinguishable from each other. As predicted, self-rating of school work was correlated highest with school self-concept, as self-rating was based on a general, overall impression of performance in school work and would be correlated with a general measure of academic self-concept.…”
Section: Results Confirmatory Factor Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…School self-concept was positively correlated with both reading and maths self-concepts (rs = .71 and .74 respectively) and with both non-academic self-concepts -art and physical self-concepts (rs = .46 and .42 respectively). The correlation between reading and maths self-concepts are high (r = .48), compared to previous research (e.g., Yeung & Lee, 1999;Yeung & Wong, 2004), but this was consistent with the prediction that they would be clearly distinguishable from each other. As predicted, self-rating of school work was correlated highest with school self-concept, as self-rating was based on a general, overall impression of performance in school work and would be correlated with a general measure of academic self-concept.…”
Section: Results Confirmatory Factor Analysissupporting
confidence: 88%
“…They suggested that self-concept is highly structured, multifaceted, and hierarchical. Subsequently, numerous researchers have found strong support for this structure (e.g., Marsh & Craven, 2006;Yeung et al, 2000;Yeung & Wong, 2004). In the academic domain, students' self-concepts are primarily their self-perceptions about themselves in academic work and these perceptions influence academic behaviours and educational outcomes.…”
Section: Importance Of Self-conceptmentioning
confidence: 99%
“…It will explore three of the five dimensions that make up the theoretical model selected: the academic, the social and the emotional dimensions. Although, as mentioned earlier, self-concept functions in separate domains and consequently, research into self-concept should be carried out at the domain-specific level (Marsh, Byrne, & Shavelson, 1988;Marsh & Yeung, 1996, 1998Yeung & Lee, 1999;Yeung & Wong, 2004), there are also advantages in taking a more holistic perspective (Mercer, 2011). If we want to understand the nature and content of a learner's EFL selfconcept, it should be born in mind that learners often refer to other domains, which they perceive as important and related, when describing themselves as EFL learners.…”
mentioning
confidence: 99%
“…To this end, research into self-concept has now started attracting attention of researchers in the domain of language learning although such interest has been limited (Mercer, 2011;Lau et al 1999;Yeung & Wong, 2004;Kumazawa, 2013). In one such study, Mercer (2011) asserted that one's self-concept in language learning may exhibit complexities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Lau et al's study is of importance in establishing the possible existence of a distinct EFL self-concept. Another study on self-concept, which also addresses distinctiveness of self-concepts in EFL, was carried out by Yeung & Wong (2004) who examined the distinctiveness of the verbal self-concepts for primary and high school teachers in Hong Kong speaking English, Cantonese and Mandarin. Their findings suggest that a single verbal self-concept could not adequately represent multilingual students and they call for research to account for differing distinct self-concepts specific to each language.…”
Section: Literature Reviewmentioning
confidence: 99%